2012
DOI: 10.1088/0960-1317/22/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

Portable oral cancer detection using a miniature confocal imaging probe with a large field of view

Abstract: We demonstrate a MEMS micromirror enabled handheld confocal imaging probe for portable oral cancer detection, where a comparatively large field of view (FOV) was generated through the programmable Lissajous scanning pattern of the MEMS micromirror. Miniaturized handheld MEMS confocal imaging probe was developed, and further compared with the desktop confocal prototype under clinical setting. For the handheld confocal imaging system, optical design simulations using CODE V R R shows the lateral and axial resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Prior studies have shown that 2D electrostatic micro-scanning mirrors can be realized by either gimbaled [12,27] or gimbal-less [28] microstructures. A gimbal typically occupies a large area to achieve independent scanning directions, leading to a reduced fill factor which may not be desirable for some applications [29].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that 2D electrostatic micro-scanning mirrors can be realized by either gimbaled [12,27] or gimbal-less [28] microstructures. A gimbal typically occupies a large area to achieve independent scanning directions, leading to a reduced fill factor which may not be desirable for some applications [29].…”
Section: Introductionmentioning
confidence: 99%
“…because of the high cost of the equipment, screening for detection of various cancer forms is not a common procedure [2]. at polyclinics, there is a need for low cost, small, hand-held probes that can be used to monitor the existence of lesions in tissues, for example, prostate cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several optical imaging modalities, such as confocal microscopy, [8][9][10][11][12] high resolution microendoscopy (HRME), [13][14][15] and optical coherence tomography (OCT), [16][17][18][19][20][21][22] have been proposed as methods for noninvasive "optical biopsy" to improve the accuracy of oral cancer screening. Reflectance and fluorescence confocal microscopy have demonstrated the ability to provide subcellular resolution of optically sectioned images within the epithelial layer due to native tissue contrast or when used with topically applied or intravenous contrast agents.…”
Section: Introductionmentioning
confidence: 99%
“…Reflectance and fluorescence confocal microscopy have demonstrated the ability to provide subcellular resolution of optically sectioned images within the epithelial layer due to native tissue contrast or when used with topically applied or intravenous contrast agents. [8][9][10][11][12] However, these systems are expensive and typically involve custom-designed high numerical aperture optics, which are challenging to miniaturize. HRME is a simple, low-cost approach which can also provide subcellular resolution en face images of epithelial tissue, albeit without intrinsic optical sectioning.…”
Section: Introductionmentioning
confidence: 99%